Social Psychological Aspects of Development of Creative Skills of School Students (Journal of Pedagogical Inventions and Practices, 2023)
In this article, the formation of skills and abilities from the school age, especially the socio-psychological aspects of the development of creativity during the student's childhood, is discussed in order to increase the creative competence of schoolchildren.